Understanding Why Tourists Who Share Travel Photos Online Give More Positive Tourism Product Evaluation: Evidence From Chinese Tourists - Tang, Xiuyuan; Gong, Yanping; Chen, Chunyan; Wang, Suying; Chen, Pengfei (Frontiers in Psychology, 2022)
This study tested a conceptual model in which photo-sharing behavior during travel elicits tourists’ emotional state, and in turn improves evaluation of the tourism product. The research results in the context of tourist attractions and restaurants provide support for the proposed model. Specifically, tourists' photo-sharing behavior was significantly associated with more positive product evaluation, both directly and indirectly via the emotion of pleasure. These associations were stronger when the interdependent self-construers had good social experience. The results provide practical guidance for marketers to developing marketing strategy.